Sistem Deteksi Perpindahan Kendaraan Bermotor Berdasarkan Data GPS dan Sensor IMU Menggunakan Naive Bayes - Wirafadil Nugraha; Dahnial Syauqy; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The security system in vehicles is something that must be considered because vehicles are often stolen which results in losses to the vehicle owner. Ease of control and a security system that can be monitored using only one communication device such as a mobile phone that can support a wireless connection is an opportunity to develop a vehicle security system. By designing a vehicle displacement detection system based on GPS data and the IMU sensor, it will become a more accurate tool to determine the condition of vehicles. In order for the system to classify the current situation more accurately, the Naive Bayes algorithm is applied. The use of GPS data in this study uses the NEO-6M module because a vehicle must be closely related or always have a coordinate location as long as it is within satellite coverage. This data is used as input along with data from the IMU sensor used in this study using the GY-61 accelerometer sensor. From this research test, the NE0-6M module has an accuracy value of 99.99%, the GY-61 sensor has an accuracy of 87,68%, and the SIM800 module can functionally run well. In the classification process that using Naive Bayes, an accuracy of 95% is obtained.